Lower sex hormone levels are associated with more chronic musculoskeletal pain in community-dwelling elderly women. Issue 7 (July 2016) - de Kruijf, Marjolein; Stolk, Lisette; Zillikens, M. Carola; de Rijke, Yolanda B.; Bierma-Zeinstra, Sita M.A.; Hofman, Albert; Huygen, Frank J.P.M.; Uitterlinden, Andre G.; van Meurs, Joyce B.J.
Abstract : Abstract: Chronic pain is more prevalent in women than in men, with increasing differences between sexes in advanced age. This could be caused by differences in sex hormone levels. We therefore studied the relationship between sex hormones and the prevalence and incidence of chronic pain. The association between sex hormone levels and chronic pain was examined in 9717 participants aged 45 years and older from the Rotterdam Study, a population-based study. Chronic pain was defined as pain in the lower back, hands, knees and/or hips for at least 3 months. Sex hormone levels included estrogen, testosterone, androstenedione, and 17-hydroxyprogesterone. Relationships between hormones and prevalent and new onset chronic pain were analyzed using linear and logistic regression, stratified by gender. Women with androstenedione or estradiol levels in the lowest tertile had more chronic pain (odds ratio, 1.20; 95% CI, 1.03-1.39 and odds ratio, 1.27; 95% CI, 1.10-1.48, respectively). Mean estradiol levels were lower among men with chronic pain (mean difference −3.88 pmol/L; P = 0.005). Lowest tertile 17-hydroxyprogesterone in women was associated with 38% more new onset pain. All these associations were independent from age, body mass index, health and lifestyle factors, and osteoarthritis. Lower sex hormone levels are associated with chronic musculoskeletal pain, independent from lifestyle and health-related factors, in community-dwelling elderly women. These results suggest that sex hormones play a role in chronic pain and should be taken into account when a patient presents with chronic pain. Therefore, sex hormones may be a potential treatment target for these patients. Abstract : Supplemental Digital Content is Available in the Text.Lower sex hormone levels are associated with chronic musculoskeletal pain, independent from lifestyle and health-related factors, in community-dwelling elderly women.